Health information-seeking among Latino newcomers - an exploratory study - Christina Courtright (Information Research: An International Electronic Journal)
ntroduction. This exploratory study examines health information-seeking practices among Latin American newcomers to a small city in the United States. The framework locates these practices within social networks, the local institutional context and the use and non-use of information technologies. Method. Semistructured interviews were conducted in Spanish with seven immigrant workers. Interviews elicited incidents of both purposive seeking and accidental encountering of health information. Analysis. Data were coded for reference to social networks, strengths of social networks, and perceptions and uses of institutions, organizations, and technologies, treating the information incident as unit of analysis. Results. Information seeking is often assisted by both social networks and key institutions, yet the quality of the information transmitted through social networks is apt to be uneven, and newcomers are unable to obtain an adequate overview of local health care for improved decision-making. Of particular interest is the finding that the local information environment has evolved significantly in response to growing demand for Spanish-language and low-income services. Conclusion. It is particularly important for information behaviour researchers to examine the dynamic interactions among study populations and their information environments over time.